Impact of Al-Rasheed Power Plant Effluents on Biodiversity of Benthic Fauna in Tigris River, Southern Baghdad - Nashaat, Muhanned Remzi; Radhi, Assel Ghazi; Mohammad, Amal Abbas; Reassn, Kareem Hameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Quantitative and qualitative composition of benthic invertebrate communities was studied during the period from January to December2012 at four stations that were selected on the Tigris River at Baghdad Province. One of the stations S2 located near Al-Rasheed Power Plant (RPP) to represent the ecological features of the plant site, whereas other stations, S1 were located at  the upstream of the RPP as a control station to investigate the ecological characters of the Tigris River.  Moreover, the two other stations S3 and S4 were located down to the impact of RPP to reflect the possible effects of the plant on the ecology of the river by comparison with the control stations. The present study recorded 44 taxa belong to 4 order which are: 11 taxa belonged to Annelida(Oligochaeta) which recorded the highest percentage73% of the total number of benthic invertebrates, 18 taxa belong to Arthropoda with 9%, 11 taxa belonging to Mollusca with 13%, 4 taxa belong to Nematoda with 5%, monthly density ranged 325 â€“ 64987 Ind. /m2 at all stations. Generally the result of biodiversity indicators shows the negative effect of thermal effluent of RPP on benthic invertebrate community at S2.